Proses Rekrutmen dan Pelatihan Dalam Meningkatkan Kinerja Karyawan pada UMKM Bebek Komet - Siti Dita Pratiwi; Wilda Nur Fatimah; Dwi Epty Hidayaty; Santi Pertiwi Hari Sandi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
In this era of globalization, quality human resources are needed because the benchmark for the success and failure of a business is very dependent on the quality of its human resources. These resources support organizations with work, talent, creativity, quality human resources determined by a good recruitment and training system. Recruitment is a struggle to find workers in order to get as many prospective employees as possible, so that as a result the industry has the opportunity to ensure that prospective employees have good standards within the company. The subject of observation is the Comet Duck Shop. The method we use is descriptive using observative. The results we have are in the form of data in the form of various stages of the recruitment and training process at Kedai Bebek Comet. Starting from the process of disseminating the required position information, the process of selecting prospective employees, to using the job training process. The purpose of this observation is to evaluate HR management at the Bebek Comet MSME listed in the series of activities provided by new employees. Based on the results of the interviews, providing an attention that results in the quality of employee performance can be fulfilled.